TWO-DIMENSIONAL CONTACT PROBLEM FOR PLATE IN ELASTIC PLANE SLOT - S. V. Bosakov (Наука и техника)
The paper contains a solution of the contact problem for a elastic plate in a slot of infinite plane using a method of orthogonal polynomials. A peculiar feature is exactly developed in contact stresses at plate edges. The given results can be applied for calculation deep anchor plates  and embedded inserts of reinforced structures.